Estonia and Kazakhstan: Financial and economic fate of economies after the collapse of the USSR - Nazym Yembergenkyzy; Beata Fałda (Financial Internet Quarterly, 2022)
The collapse of the USSR significantly affected the economic and political situation of all the republics which gained sovereignty as a result. Among them were countries such as Estonia and Kazakhstan. This article considers whether these countries have coped with the new political conditions. Using known economic indicators, a comparison was made of the economic and financial situation of both countries, pointing to the potential causes of diversification of their socio-economic development. Currently, Estonia is considered the most developed country of the 15 former members of the USSR, and Kazakhstan is in 5th place. The research carried out in this paper shows that the current economy of Kazakhstan is clearly moving away from that Estonia needs radical measures to achieve economic acceleration. The authors, analyzing the strategic activity of Estonia and Kazakhstan and the independence of financial management, concluded that these have had a significant impact on the current state of economic and financial development of the countries in question.
Keywords: E60; G00; G50; H00; 330; Kazakhstan; Estonia; economic transition; financial and economic development; political transformation